Szara strefa a redystrybucja PKB - implikacje, uwarunkowania - Buszko, Andrzej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The main objective of this paper is to establish the relationship between the size of the shadow economy and the level of redistribution of GDP. Pearson correlation coeffcient was used for small samples The hypothesis that the level of public expenditure is strongly stochastically positively correlated with the level of the shadow economy has been confidently verified. The study included Poland, Hungary, the Czech Republic, Slovakia and Bulgaria between 1995-20014. The article describes the categories of the shadow economy and the conditions of its creation in the context of the macroeconomic effects of redistribution of GDP.